THE ICE-BREAKER ACTIVITYIN TEACHING ENGLISH TO YOUNG LEARNERS' - Rina Mariana, - (2010)
The paper entitled The Ice-Breaker Activity in Teaching English to Young Learners was aimed to investigate the strategies employed in the ice-breaker activity and the obstacles encountered by the teachers during the activity. The study employed descriptive method where the data were gained through examining archival documents i.e. lesson plan, classroom observation, and interview. The findings show that the teachers under investigation did employ three strategies in ice-breaker activity; visualization through pictures and realia, brainstorming, and physical activities through games and pair-work. Regarding the obstacles encountered by teachers during the ice-breaker activity, the study found the obstacles are unclear instruction, students' enthusiasm, teachers' creativity related to the media making and time management. This study concludes that ice-breaker activity can help teachers in creating a positive classroom atmosphere. Accordingly, there are at least three aspects that need to be taken into consideration in order to achieve it: design of ice-breaker, optimizing teachers' role and their competence, and promoting students' participation in the classroom.